Studying the Computing Implementation of Interactive Musical Notation (Música Hodie, 2013)
Formalized music is usually based on the asynchronous creation of musical structures by the composer, that are later expressed in the form of music notation. This can also be considered as an algorithmic structure that, once executed by the musical performer, reaches the state of sonic art; the music per se, formed by the organization of sounds along time. This is perceived by the listener whose cognition attributes to it a personal meaning. This article introduces a computational process that aims to artistically explore the inversion of its natural order, respectively given by: the composer, the performer and the listener. Throughout a computational model, listener perception data is retrieved and used to control the dynamic creation of musical notation in real-time. After this process is over, the final result is a structured musical notation, generated by a self-organizing process given by the systemic interaction of independent agents, that are: the computer, the composer, the performer and the listeners. Keywords: Musical notation; Computer music; Interactive music.